Female Heart Health: Is GPER the Missing Link? - Groban, Leanne; Tran, Quang-Kim; Ferrario, Carlos M.; Sun, Xuming; Cheng, Che Ping; Kitzman, Dalane W.; Wang, Hao; Lindsey, Sarah H. (Frontiers in Endocrinology, 2020)
The G Protein-Coupled Estrogen Receptor (GPER) is a novel membrane-bound receptor that mediates the nongenomic actions of the primary female sex hormone 17-estradiol. Studies over the past two decades have elucidated the beneficial actions of this receptor in a number of cardiometabolic diseases. This review will focus specifically on the cardiac actions of GPER, since this receptor is expressed in cardiomyocytes as well as other cells within the heart and most likely contributes to estrogen-induced cardioprotection. Studies outlining the impact of GPER on diastolic function, mitochondrial function, left ventricular stiffness, calcium dynamics, cardiac inflammation, and aortic distensibility are discussed. In addition, recent data using genetic mouse models with global or cardiomyocyte-specific GPER gene deletion are highlighted. Since estrogen loss due to menopause in combination with chronological aging contributes to unique aspects of cardiac dysfunction in women, this receptor may provide novel therapeutic effects. While clinical studies are still required to fully understand the potential for pharmacological targeting of this receptor in postmenopausal women, this review will summarize the evidence gathered thus far on its likely beneficial effects.